Assessment of the effectiveness of a sublingual, ergogenic spray on muscle strength and power - Jacobson, B. H.; Smith, D. B.; Warren, A. J.; Glass, R. G.; Kline, C. l; Fedick, J. L; Stemm, J. (The Journal of Strength and Conditioning Research, 2009)
Nutrients, chemicals, and drugs may be applied sublingually to provide faster absorption. Sublingual absorption occurs when a substance comes in contact with the buccal mucosa, where it diffuses through a membrane of the dense capillaries. The purpose of this study was to assess the effectiveness of a sublingual, ergogenic product containing vitamins, minerals, amino acids, and a coenzyme on muscle performance. National Collegiate Athletic Association Division I linemen (n = 23) voluntarily participated in the study. All participants (20.11 ± 1.45 years, 132.1 ± 9.85 kg, 191.19 ± 3.85 cm) were tested on 102.1 kg (225 lb) bench press repetitions, vertical jump, and grip strength. One week later, participants were either a placebo or the experimental treatment before they were tested again. Repeated-measures analyses of variance (ANOVAs) yielded a significant (p = 0.046) gain for the bench press. A Newman-Keuls post hoc test revealed a significant change in the treatment group but not in the placebo group. While the treatment group demonstrated greater improvement over the placebo group for each of the remaining variables, none were significant: vertical jump (p = 0.65) and grip strength (p = 0.74). The inconsistency of the results may be due to several factors. First, the spray may not be an ergogenic agent; second, the standardized dose may be too small for those weighing =290 lb and should be administered based on weight. Furthermore, the coenzyme and amino acids may not possess the molecular size, solubility, chemical stability, or hydrophilic character to be easily absorbed. Lastly, the data were generated by field tests and may not be sensitive enough to elicit subtle responses.